2017
DOI: 10.1128/mbio.00644-17
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Gene Transfer Dynamics in the Ancient Bacterial GenusStreptomyces

Abstract: Lateral gene transfer (LGT) profoundly shapes the evolution of bacterial lineages. LGT across disparate phylogenetic groups and genome content diversity between related organisms suggest a model of bacterial evolution that views LGT as rampant and promiscuous. It has even driven the argument that species concepts and tree-based phylogenetics cannot be applied to bacteria. Here, we show that acquisition and retention of genes through LGT are surprisingly rare in the ubiquitous and biomedically important bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
94
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(104 citation statements)
references
References 67 publications
10
94
0
Order By: Relevance
“…Metagenomic analyses have shown that such gifted actinobacteria are a feature of natural habitats [57,58]. Creative cultivation techniques are available for the isolation of rare and novel actinobacteria with large genomes [27,59], though there is a need to marry innovative selective isolation procedures with the ecology of target organisms [60][61][62][63], as demonstrated by adaptations shown by Salinispora and Streptomyces strains [64,65]. There is also a need to obtain complete genome sequences from especially gifted actinobacteria [33,34] for systematic genome mining for new molecules.…”
Section: Genome Analysismentioning
confidence: 99%
“…Metagenomic analyses have shown that such gifted actinobacteria are a feature of natural habitats [57,58]. Creative cultivation techniques are available for the isolation of rare and novel actinobacteria with large genomes [27,59], though there is a need to marry innovative selective isolation procedures with the ecology of target organisms [60][61][62][63], as demonstrated by adaptations shown by Salinispora and Streptomyces strains [64,65]. There is also a need to obtain complete genome sequences from especially gifted actinobacteria [33,34] for systematic genome mining for new molecules.…”
Section: Genome Analysismentioning
confidence: 99%
“…It is within these arm regions that most of the specialized metabolic clusters are found. Recent work has 47 revealed that specialized metabolic clusters are over-represented as horizontally-transferred elements 48 in the streptomycetes (McDonald and Currie, 2017), and that in the closely-related Salinospora, lateral 49 gene transfer is a major driver of specialized metabolism (Ziemert et al, 2014). 50…”
Section: Introduction 13mentioning
confidence: 99%
“…The microbial expansin phylogeny indicates that HGT has been an important process shaping the distribution of expansins among microorganisms, and that expansin gene exchange is ongoing. In some cases, the presence of expansin genes in most sequenced species within a group (such as Myxobacteria, Xanthomonadaceae, and the Pectobacterium and Dickeya group of Entobacterial plant pathogens) suggests that original acquisition of an expansin likely occurred in a common ancestor of these taxa before these groups diversified (105). In other species – notably several plant pathogens – acquisition of an expansin likely occurred on more recent ecological time scales.…”
Section: Discussionmentioning
confidence: 99%